STYLISTIC MECHANISMS OF LEXICAL ECONOMY: A COMPARATIVE ANALYSIS OF ENGLISH AND UZBEK - Omonov Baxtiyor Uktamovich (Ta'lim innovatsiyasi va integratsiyasi, 2026)
This study provides a comparative analysis of lexical economy mechanisms in English and Uzbek languages. Lexical economy—the linguistic tendency to convey maximum meaning with minimal resources—manifests differently across languages due  to  typological  characteristics.  Through  systematic  analysis  of  contemporary corpora,  this  research  demonstrates  that  English,  as  an  analytic  language,  employs syntactic compression, abbreviation, and metaphorical expression, while Uzbek, as an agglutinative  language,  utilizes  morphological  synthesis,  contextual  ellipsis,  and idiomatic condensation. The investigation reveals how structural differences influence economic expression, offering insights into cognitive and communicative strategies. These  findings  have  practical  implications  for  translation,  language  pedagogy,  and cross-cultural communication, highlighting the need for typology-sensitive approaches in applied linguistics.